Socially responsible innovation in security critical reflections - Burgess, J. Peter 1961-; Reniers, Genserik 1974-; Ponnet, Koen; Hardyns, Wim; Smit, Wim A. (Routledge new security studies, 2018)
"This book examines the possibility of socially responsible innovation in security, using an interdisciplinary approach. Responsible innovation in security refers to a comprehensive approach that aims to integrate knowledge related to stakeholders operating at both the demand and the supply side of security - technologists, citizens, policymakers and ethicists. Security innovations can only be successful in the long term if all the social, ethical and ecological impacts, threats and opportunities, both short term and long term, are assessed and prioritized alongside technical and commercial impacts. The first part of this volume focuses on security technology innovation and its perception and acceptance by the public, while the second part delves deeper into the processes of decision-making and democratic control, raising questions on the ethical implications of security ruling. This book will be of much interest to students of critical security studies, sociology, technology studies and IR in general"...